TINJAUAN MANAJEMEN SUMBER DAYA MANUSIA YANG MEMPENGARUHI KINERJA: SEBUAH AGENDA PENELITIAN - Eri Novari (GoAcademica Research dan Publishing, 2020)
There is increasing evidence supporting the relationship between so-called high-performance or high-commitment human resource management practices (HRM) and various measures of organizational performance. However, it is not clear why this relationship exists. This paper argues that in order to provide a convincing explanation about this association, we need to improve the theoretical and analytical framework in three main areas namely the nature of HRM, and especially the reasons for a specific list of HR practices; the nature of organizational performance; and the relationship between HRM and performance. A model is presented to explore this connection. Existing literature on HRM and performance is reviewed based on analysis to identify key gaps in knowledge and help focus further research priorities.